Lubelski rękopis "Dekretu Gracjana" - Burczak, Krzysztof (Vox Patrum, 2008)
The library of the John Paul II Catholic University of Lublin possesses particularly interesting manuscript of "Decretum Gratiani". The work dates from the 13th century and was made in Toulouse. Probably in the 15th century the French Benedictines handed the work over to their brothers in Monte Calvo (= Łysa Góra) in Poland. The manuscript was in the private collection of Piotr Moszyński in Krakow. On May 25, 1923, his son, Count Jerzy Moszyński, donated the work to the library of the University in Lublin. The manuscript is in good condition: contains 308 sheets of parchment and its cover is made of wood bound in leather. The manuscript contains 38 thumbnails. The text of the decree and the glossary of Johannes Teutonicus are in black ink. The headings are in red ink. The initials are written in red and blue ink. The text contains numerous inscriptions from the 18th century. The manuscript is of particular interest to scientists because of the use of paleae. The manuscript of the decree in Lublin contains 73 such paleae.